Moving object detection and tracking in video surveillance system - Ahmed, Sabri M.A.A.; Khalifa, Othman Omran (Shriganganagar Rajasthan, India, 2016)
Detecting and tracking objects in crowded areas is a challenging issue in the field of Video surveillance system. Nowadays the increase of digital video cameras, and the availability of video storage and high performance video processing hardware, opens up conceivable outcomes for tackling many video understanding problems. Developing a real-time video understanding technique which can process the large amounts of data becomes very important. The object detection first step used in surveillance applications aims to separation of foreground objects from the background. Many algorithms proposed to solve the problem of object detection, however, it still lack of tracking multiple objects in real time. Object tracking used to find a moving object detected in motion detection stage from one frame to another in an image sequence. This paper focuses on review of various techniques used in object detection and object tracking.